A study of the statutory provisions that facilitate the variation of labour standards in South Africa - Harper, Lionel Seymour (Institute of Development and Labour Law, 2025)
This dissertation treats the progressive development of labour standards in the South African labour market and it examines the extent to which the current labour standards can. Be varied by the relevant statutory institutions. It also endeavours to show - how protective standards have been incorporated into the South African industrial system, how labour standards are varied by the various statutory institutions, - how labour market flexibility and protection standards are compatible, and - how equality and skills are integral to social economic development. As a corollary it looks at the extent to which South African labour legislation provides protection for atypical workers and other vulnerable categories of workers, such as blacks (Africans, Coloureds and Indians), women and disabled persons.